2013
DOI: 10.4049/jimmunol.1301005
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Target of Rapamycin Activation Triggers IL-4 Production and Necrotic Death of Double-Negative T Cells in Patients with Systemic Lupus Erythematosus

Abstract: The mechanistic target of rapamycin (mTOR) is recognized as a sensor of mitochondrial dysfunction and effector of T-cell lineage development, however, its role in autoimmunity, including systemic lupus erythematosus, remains unclear. Here, we prospectively evaluated mitochondrial dysfunction and mTOR activation in PBL relative to SLE disease activity index (SLEDAI) during 274 visits of 59 patients and 54 matched healthy subjects. Partial least square-discriminant analysis identified 15 of 212 parameters that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
132
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 135 publications
(143 citation statements)
references
References 62 publications
(84 reference statements)
9
132
0
Order By: Relevance
“…These results are in line with earlier studies demonstrating enhanced mTOR activation in lupus T cells (13,14).…”
Section: Cells In Pediatric Patients With Lnsupporting
confidence: 83%
See 3 more Smart Citations
“…These results are in line with earlier studies demonstrating enhanced mTOR activation in lupus T cells (13,14).…”
Section: Cells In Pediatric Patients With Lnsupporting
confidence: 83%
“…Moreover, the inhibition of mTOR by rapamycin reduces disease activity in patients with SLE (12). Previous studies also demonstrated that double-negative T cells from rapamycin-treated SLE patients display reduced necrosis and IL-4 production (14). Additionally, the PI3K/Akt/mTORC1 pathway controls the differentiation of Th17 cells by regulating the nuclear translocation of RORg and other factors (37).…”
Section: Cd45ramentioning
confidence: 99%
See 2 more Smart Citations
“…This regulatory T cells together with CD4+CD25-cells increased STAT3 and STAT5 phosphorylation and enhance the differentiation of CD8+ T cells into memory cells in mice inoculated with lymphocytic choriomeningitis virus. Prospective clinical trial in SLE patients with sirolimus is ongoing [74][75][76]. Scleroderma m-TOR can plays a role in fibrotic diseases and autoimmunity, and blockade of the mTORC pathway through blocking the profibrotic effects of TGF-β can play a part in the treatment of scleroderma (or systemic sclerosis), however, this approach is currently under investigation [77].…”
Section: Systemic Lupus Erythematosus In Murine Lupus Models and Humanmentioning
confidence: 99%